A Rare Case of Proximal Junctional Failure with Delayed Infection after Adult Spinal Deformity Surgery: A Report of Two Cases - Takuro Iwami; Mitsuru Yagi; Eijiro Okada; Satoshi Suzuki; Satoshi Nori; Osahiko Tsuji; Narihito Nagoshi; Kota Watanabe; Nobuyuki Fujita; Masaya Nakamura; Morio Matsumoto (Case Reports in Orthopedics)
Proximal junctional failure (PJF) is one of the most devastating complications that develop after adult spinal deformity (ASD) surgery. Here, we report 2 rare cases of PJF accompanied by delayed infection after ASD surgery with a review of the relevant literatures. Late-onset infection is an infrequent complication despite acute postoperative infection is common after posterior spinal instrumentation and fusion. Among them, delayed onset pyogenic spondylitis of the adjacent vertebra to the instrumented vertebrae is an extremely rare phenomenon. We do not have a clear explanation for this pathology. Since the delayed infections developed not in the fused segments but in the adjacent vertebra, the cause of the first case can be speculated as stimulation of low-virulent organisms to fester and hematogenous seeding and that of the second case as metal fretting and a sterile inflammatory response causing hematogenous microbial seeding, respectively. Additional studies on this phenomenon are warranted to elucidate the pathogenesis of this complication.